CATECHISM WITHOUT GOD: LEGAL BASIS AND IDEOLOGICAL PREMISES OF TEACHING MARXISM IN SCHOOLS OF SOCIALIST YUGOSLAVIA FROM 1945 TO 1991: ZAKONSKI OSNOV I IDEOLOŠKE PREMISE MARKSISTIČKOG OBRAZOVANJA U ŠKOLAMA SOCIJALISTIČKE JUGOSLAVIJE OD 1945 DO 1991. - Božić, Marko D (Pravni zapisi, 2022)
The paper sketches a general timeline and defines key milestones in some fifty years long teaching Marxism within the state school system of the socialist Yugoslavia. The research relies primarily on relevant legal framework, especially the School Reform Acts of 1958 and 1974, and associated doctrinal writings. Through discourse analysis of these legal and doctrinal sources, the paper discloses the evolving role and purpose of teaching Marxism as an institutionalized belief that was meant to contend the traditional religion. By questioning the experience of this so-called school-Marxism, the study contributes to a better understanding of socialist secularism as a historical phenomenon, potentially also instigating new attempts at reconsidering whole series of old, yet still persisting controversies, such as interrelation of science and atheism, the role and place of moral education, or religious neutrality of school curricula.